2008
DOI: 10.2341/07-bl2
|View full text |Cite
|
Sign up to set email alerts
|

Placing Dental Composites—A Stressful Experience

Abstract: The inevitable generation of stress in dental composites that undergo polymerization shrinkage continues to mandate a precise and careful placement technique to ensure successful clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
191
0
18

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(211 citation statements)
references
References 83 publications
2
191
0
18
Order By: Relevance
“…37 According to Hooke's law, stress is equal to the elastic modulus multiplied by the strain. 40 Thus, lower shrinkage, combined with the lower elastic modulus of both SIL and AL, can explain the decreased stress within the composite structure. A low modulus of elasticity of a material was not necessarily associated with high bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…37 According to Hooke's law, stress is equal to the elastic modulus multiplied by the strain. 40 Thus, lower shrinkage, combined with the lower elastic modulus of both SIL and AL, can explain the decreased stress within the composite structure. A low modulus of elasticity of a material was not necessarily associated with high bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, light-curing resins are frequently used in adhesive dentistry to bond ceramic restorations such as inlays, overlays, or crowns to dental hard tissues. However, despite widespread application, these resins suffer from shrinkage [4] and incomplete curing of the resin [5].…”
Section: Introductionmentioning
confidence: 99%
“…The current goal of the manufacturers of resin composite restorative materials remains improvement or elimination of contraction stress-possibly through low or non-shrinking monomers. 17 Research has shown that the amount of polymerization shrinkage may be reduced by an increase in filler particles. 8 Filler loading can be deceiving, however, because it may not be indicative of the presence of pre-polymerized filler particles.…”
mentioning
confidence: 99%